2004
DOI: 10.1248/bpb.27.544
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 Reverse Transcriptase and Protease by Phlorotannins from the Brown Alga Ecklonia cava

Abstract: The reverse transcriptase (RT) of human immunodeficiency virus type-1 (HIV-1) converts the single-stranded (ϩ) viral RNA genome into a double-stranded proviral DNA prior to its integration into the host genomic DNA. The RT is a multifunctional enzyme with three recognized enzymatic activities of RNA-dependent DNA polymerase (RDDP), DNA-dependent DNA polymerase (DDDP), and ribonuclease H activities. HIV-1 protease is an aspartic protease required for the proteolytic processing of the large Gag and Gag-Pol viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(113 citation statements)
references
References 20 publications
(26 reference statements)
1
103
0
6
Order By: Relevance
“…27) Numerous bioactivities of phlorotannins have been reported up to date such as antioxidant, anti-inflammatory, 28) antibacterial, 29) and anti-MMP activities. 30) Furthermore, Ahn et al 31) claimed that phloroglucinol derivative 8,8'-bieckol inhibited the activity of recombinant RT and protease of HIV-1 in vitro. Artan et al 32) reported the enhanced HIV-1 inhibitory effect of a phloroglucinol derivative, 6,6′-bieckol, from E. cava.…”
Section: Discussionmentioning
confidence: 99%
“…27) Numerous bioactivities of phlorotannins have been reported up to date such as antioxidant, anti-inflammatory, 28) antibacterial, 29) and anti-MMP activities. 30) Furthermore, Ahn et al 31) claimed that phloroglucinol derivative 8,8'-bieckol inhibited the activity of recombinant RT and protease of HIV-1 in vitro. Artan et al 32) reported the enhanced HIV-1 inhibitory effect of a phloroglucinol derivative, 6,6′-bieckol, from E. cava.…”
Section: Discussionmentioning
confidence: 99%
“…Antaranya termasuklah antikoagulan, antitrombotik, antiviral, antitumor, imunomodulat, antikeradangan, pengurang lemak darah, antioksidan, aktiviti melawan hepatopati, uropati dan nefropati, perlindungan kesan gastrik dan potensi terapeutik dalam pembedahan (Ale 2012;Li et al 2008;Synytsya et al 2006). Permintaan yang tinggi daripada pengguna untuk makanan yang diproses secara minimum dan mengandungi bahan pengawet semula jadi, kajian secara mendalam terhadap pengekstrakan antioksidan alternatif semula jadi dan sebatian antimikrob semakin giat dijalankan (AbuGhannam & Gupta 2010;Ahn et al 2004;Andarwulan et al 2010;Apostolidis, Ayaz et al 2008;Chew et al 2008;Cox et al 2008;Rajauria et al 2010).…”
Section: Pengenalanunclassified
“…All compounds were isolated on the basis of retention times. Phlorotannin content was assessed by measuring the dimensions of HPLC peaks and comparing these with those of and Glombitza, 1986) and exhibit a variety of physiological activities, including antioxidant (Yoon et al, 2011), antidiabetic (Okada et al, 2004), antimicrobial (Eom et al, 2011), anti-inflammatory Kang et al, 2013), and antihypertensive properties; they inhibit melanogenesis (Heo et al, 2009), metalloproteinases , and reverse transcriptase (Ahn et al, 2004), induce quinine reductase (Yoon et al, 2013), and exert depressive effects on the central nervous system (Cho et al, 2012). However, E. bicyclis has a bitter tannin-rich taste; it is also tough in texture and is thus unappetizing.…”
Section: Quantification Of Phlorotannins In Abalonementioning
confidence: 99%